2015
DOI: 10.2214/ajr.14.13960
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Ablation: Normal Imaging Appearance and Delayed Complications

Abstract: Radiologists should recognize the normal imaging findings in patients who have undergone endometrial ablation, be aware of the causes of treatment failure, and accurately identify delayed complications associated with these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The use of ablation sites was a novel approach in this study to provide a system for localization of the HT targets as well as positive controls, both of which are absent from the previous studies. The hyper-intensive lesion shown in the contrast-enhanced MR were consistent with results from a prior publication [45], and matched the severe hemorrhage and fluid-filled cavities observed in the macroscopic and histological results. With that said, some studies found post-ablation targets to be seen as non-perfused areas in the MR images, as opposed to the hyper-intense regions seen here [46][47][48].…”
Section: Discussionsupporting
confidence: 90%
“…The use of ablation sites was a novel approach in this study to provide a system for localization of the HT targets as well as positive controls, both of which are absent from the previous studies. The hyper-intensive lesion shown in the contrast-enhanced MR were consistent with results from a prior publication [45], and matched the severe hemorrhage and fluid-filled cavities observed in the macroscopic and histological results. With that said, some studies found post-ablation targets to be seen as non-perfused areas in the MR images, as opposed to the hyper-intense regions seen here [46][47][48].…”
Section: Discussionsupporting
confidence: 90%
“…Endometrial ablation procedures are performed for the treatment of menorrhagia in patients who present with abnormal uterine bleeding and have unsuccessful medical therapy (63). The main indication for endometrial ablation is premenopausal chronic ovulatory menorrhagia.…”
Section: Uterine and Ft Interventions Postablation Tubal Sterilizatiomentioning
confidence: 99%
“…Endometrial ablation is a procedure performed to destroy the endometrium in women with premenopausal menorrhagia who do not want to preserve fertility or undergo hysterectomy. Current methods include nonresectoscopic techniques using thermal, cryo-, radiofrequency, and microwave ablation, as well as older hysteroscopic techniques such as laser, rollerball, wire-loop, and vaporizing electrode ablation (23). These procedures cause scarring and adhesions from the healing-denuded myometrium, resulting in occlusion of the endometrial canal.…”
Section: Endometrial Ablationmentioning
confidence: 99%
“…Accumulation of blood in an obstructed canal can cause severe pain. The blood can fill the endometrial canal, localize to the cornua, or create a hematosalpinx in cases of prior tubal ligation (postablation tubal sterilization syndrome) (23).…”
Section: Endometrial Ablationmentioning
confidence: 99%
See 1 more Smart Citation